Flipped Learning and E-Learning as Training Models Focused on the Metaverse - Jesús López-Belmonte; Santiago Pozo-Sánchez; Noemí Carmona-Serrano; Antonio-José Moreno-Guerrero (Emerging Science Journal, 2022)
Virtual Learning Environments (EVA) have acquired special importance in the educational field in recent years. The metaverse has been constructed as a learning space with enormous potential. As such, the immersion possibilities of the metaverse increase when compared to other methodologies that already implement technology, such as flipped learning and e-learning. In these learning environments, students require a set of specific abilities and skills. Therefore, this study aims to understand which training approach (flipped learning or e-learning) helps students acquire better skills through a teaching and learning process in the metaverse. This thesis used a pre-post quasi-experimental design of a group containing 173 Spanish high school students to achieve its aim. The data collection has been carried out by the Teaching and Learning Experiences Questionnaire (ETLQ). Among the obtained results, it is discovered that in all the dimensions analyzed, a significant relationship is observed. The greatest difference in means occurs in the LO dimension, meaning that these educational experiences directly impact the student’s academic results. It is concluded that both training approaches are adequate in preparing students for training processes carried out in the metaverse since they complement each other. Therefore, as preliminary instruction, the sequential use of these approaches is necessary when familiarizing students with a new learning reality such as the metaverse. Doi: 10.28991/ESJ-2022-SIED-013 Full Text: PDF